Mediating Character of Commitment between Brand Image and Customer Loyalty: A Study of Banking Sector of Pakistan - Jamal, Ahmed Hassan; Ali, Moazzam; Javaid, Muhammad Ehsan (Annals of Human and Social Sciences, 2024)
This paper attempts to inspect the mediating role of commitment in enhancing customer loyalty and to explore the impact of brand image on commitment, and ultimately toward customer loyalty. Survey method is employed in this study. Questionnaires were distributed to 450 respondents who have a personal bank account in any commercial bank of Pakistan. Out of 450 questionnaires distributed, 379 valid responses are analyzed in the study. The findings of the study revealed that existence of commitment enhances the impact of brand image on the loyalty of the customer. The findings of the study are useful for the marketing departments of financial institutions e.g. commercial banks so they can understand the role of building bank image to enhance customer loyalty. It is recommended that marketing strategies of the bank should focus on improving their brand image which in turn will lead to the higher customer loyalty. Banks in Pakistan may target establishing their bank image via offering range of services and their service quality so that they can ensure loyal customer that can ultimately enhance their profitability